Influência de fatores ambientais na riqueza e composição de espécies de liquens corticícolas em área de brejo de altitude e caatinga - Leite, Amanda Barreto Xavier (2013)
The lichens are symbiotic associations between a fungus, almost always an Ascomycota, and one or more species of algae or cyanobacteria. This study aimed to (i) compare the richness and composition of lichens corticolous in two forest types, Brejo de Altitude and Caatinga, in the state of Paraíba: (ii) verify if lichen species richness is influenced by biotic and abiotic factors such light, bark pH and diameter at breast height (DBH) of the host and (iii) analyze whether these biotic and abiotic factors differ between the studied areas. In two forest types, Caatinga and Brejo de Altitude, in the state of Paraíba, five transects with 100 m each were delimited, located 25 m apart from each other. In each transect, one sampling unit was delimited every 10 m, with a total of 50 points for each area. At each point the nearest tree was sampled and all lichen thalli removed in an area of 1.5 m along the stem (tree trunk) from the ground, disregarding the first 0.5 m above the ground. Species richness and composition were analized for each area. A total of 755 samples were collected, with 18 families, 44 genera and 121 species of corticolous microlichens. The Caatinga showed a greater species richness (74 species), with 50 species recorded for the Brejo de Altitude. With respect to species composition, the areas were quite different. Comparing lichen species richness in relation to biotic and abiotic factors, such as light (transmittance and total canopy openness), bark pH and diameter at breast height (DBH) of the selected host, the results showed to be significant. Between the areas, only the factors canopy openness and elevation did not obtain the same significance. The results presented here contribute to a small portion of the ecological knowledge of these microfungi, making this study an important tool for further research that will enhance and enrich Liquenology, as well as increase the knowledge about the vegetation types in the study